Application of a continuum damage mechanics (CDM)-based model for predicting formability of warm formed aluminium alloy. Issue 9 (February 2017) - Bai, Q.; Mohamed, M.; Shi, Z.; Lin, J.; Dean, T.
Abstract Predicting formability of sheet metal in warm forming condition is a challenge since warm forming is a thermo-mechanical process and formability is varied with temperature and strain rate. Current standard forming limit curves (FLCs) which have been established for fixed values of temperatures and strain rates cannot be used directly to predict the formability of sheet metal in warm/hot forming processes. In this paper, a series of experiment were carried out to establish FLCs for AA5754 at a temperature range of 200–300 °C and a forming rate of 20–300 mm/s using Argus system. Based on a set of continuum damage mechanics (CDM)-based theories, the constitutive model is implemented in Ls-Dyna user subroutine. Finite element (FE) result of strain distribution was compared with the experimental result from Argus system in terms of different strain paths. FE results have a good agreement with the experimental results, which indicates that the FE model developed can be used to predict formability for warm forming process.